Omnidirectional locomotion in a quadruped robot : a CPG-based approach - Matos, Vítor (2010)
Quadruped locomotion on rough terrain and un- predictable environments is still a challenge, where the concept of Central Pattern Generators (CPG) has brought interesting ideas. In this contribution we present a CPG design based on coupled oscillators, generating the required stepping movements of a limb for omnidirectional motion. Movements are on- line modulated through small value changes in the CPG’s parameters as required to perform the desired omnidirectional locomotion in a quadruped robot. We also present a method- ology to modulate the CPG’s parameters, reducing the control dimensionality, described in terms of the robot’s translational speed, angular velocity and walking orientation. Results show the proposed controller is well suited for the online generation and modulation of the motor patterns required to achieve the desired omnidirectional walking motion.